Pengaruh Kepercayaan, Kemudahan Penggunaan dan Kepuasan Berbelanja Online terhadap Minat Membeli Kembali Konsumen (Studi pada Pengguna Shopee di Indonesia) - Rama Rama; Muchsin Muthohar (Journal on Education, 2023)
This study aims to examine the effect of trust, ease of use, and consumer shopping satisfaction on the repurchase intention of Shopee users in Indonesia. The data analysis technique in this study was the Structural Equation Model (SEM) using Amos software version 26. The sampling technique used purposive sampling method with 200 respondents. Data collection was carried out by distributing online questionnaires using the Google form. The results of this study indicate that there is a positive influence of trust, ease of use, and consumer shopping satisfaction on repurchasing intention. Ease of use also has a positive and significant influence on consumer trust and shopping satisfaction at Shopee e-commerce.